Peculiarities of criminal proceedings materials preservation in conditions of martial law - Fomina, T. H. (Bulletin of Kharkiv National University of Internal Affairs, 2022)
Taking into account the latest legislative changes to the Criminal Procedure Code of Ukraine, the theoretical and practical issues of the preservation of criminal proceedings materials in the conditions of martial law are highlighted. The judicial practice regarding the restoration of lost materials of criminal proceedings has been analyzed. The study of the decisions entered into the Unified State Register of Court Decisions shows that the recovery of criminal proceedings materials is not yet a widespread practice, which is due to several factors. It is emphasized that the restoration of the materials of criminal proceedings in the future will depend on the availability of criminal proceedings material copies at the investigator’s, inquirer’s and prosecutor’s disposal, given that the legislative changes to Art. 615 of the Criminal Procedure Code of Ukraine are quite timely and appropriate. The list of pre-trial investigation materials that must be kept by the inquirer, investigator or prosecutor in electronic form is given. A systematic analysis of the criminal procedural legislation and legal acts made it possible to conclude that the preservation of the materials of the criminal proceedings in electronic form is possible in the case of: 1) production in electronic form using a qualified electronic signature of an official; 2) creation of a pre-trial investigation using an information and telecommunications system; 3) digitization, i.e. transformation of criminal proceedings materials into electronic format. Saving the materials of criminal proceedings in electronic form by means of digitization is currently a more accessible method, given the impossibility of fully using the «eCase» information and telecommunication system at all pre-trial investigation bodies, as well as given the limitations on the volume of procedural documents that can be produced in electronic form using a qualified electronic signature.